2020
DOI: 10.1021/acs.orglett.0c00348
|View full text |Cite
|
Sign up to set email alerts
|

C–H···Anion Interactions Assisted Addition of Water to Glycals by Sterically Hindered 2,4,6-Tri-tert-butylpyridinium Hydrochloride

Abstract: The conjugate acid of the bulky base 2,4,6-tri-tert-butylpyridine, under mild conditions, catalyzes the synthesis of silylprotected 2-deoxy-hemiacetals and their dimerized products from glycals at varying concentrations of water. The criticality of the concentration of water in the reaction outcome is indicative of a unique mechanistic pathway for the bulky pyridine salt and not via the general Brønsted acid mechanism. The various silyl-protected hemiacetals thus synthesized were successfully utilized in the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
10
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 38 publications
(53 reference statements)
5
10
0
Order By: Relevance
“…Commercially available grades of organic solvents are used for column chromatography for purifications. The known compounds 1a, 15,27 1b, 14h,28 1c, 14h,28 1d, 14h,28 1e, 15,27 1f, 14e,h,28 1g, 27,29 1h, 15,30 1i, 16,28 and 1j 30 showed characterization data in full agreement with previously reported data.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…Commercially available grades of organic solvents are used for column chromatography for purifications. The known compounds 1a, 15,27 1b, 14h,28 1c, 14h,28 1d, 14h,28 1e, 15,27 1f, 14e,h,28 1g, 27,29 1h, 15,30 1i, 16,28 and 1j 30 showed characterization data in full agreement with previously reported data.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…23 Given the significance of the sulfonamides, it is important to develop other milder methods for the direct synthesis of 2-deoxysulfonamidoglycosides. After successfully utilizing the bulky pyridine catalysis for O-and S-glycocosylation reactions, 8,9,10 here, in the current work, we present this mild and unique anion based activation catalyzed synthesis of 2-deoxy glycosylsulfonamides in a highly efficient and stereoselective fashion. Our attempts started by using 3,4,6-tri-O-(p-methylbenzyl)-D-galactal 1c and orthotoluenesulfonamide 2c as starting materials and the chloride salt 3a as the catalyst in dichloroethane as the solvent.…”
Section: Scheme 1 Earlier Studies On Sulfonamidoglycosylationmentioning
confidence: 99%
“…6,7 Due to the complete shielding of the cationic [N-H] + site by the bulky ortho-tert-butyl groups, the [N-H] + •••Cldistance is found to be unusually longer (3.10 Å) even in the solid state. 8 We hypothesized that due to the weakening of the cation-anion interactions in the sterically bulky TTBPy salts owing to the steric bulk, the anions show increased reactivity in organic solvents and can activate any third molecule, which we call as frustrated Brønsted pair reactivity. 9 The mild activation conditions have been exploited in the stereoselective synthesis of O-and S-glycosylation reactions from glycals.…”
mentioning
confidence: 99%
“…Recently, we demonstrated the unusual ability of the chloride anion associated with a sterically bulky protonated 2,4,6-tri- tert -butylpyridinium cation (the N–H···Cl distance is unusually longer, 3.1 Å) to activate the water molecule via Cl – ···H–O–H interactions, thereby utilizing mild conditions to hydrate the acid-sensitive and silyl-protected glycals. We were intrigued by the idea and were curious to understand whether such unique and mild A – ···H–O–H interactions could be utilized for the synthesis of 2-deoxy- C -glycosides or a Ferrier rearrangement using allyltrimethylsilanes as nucleophiles via the 2-deoxyoxocarbenium ion or the allyloxycarbenium ion, respectively.…”
mentioning
confidence: 99%
“…However, after a careful analysis of the 1 H NMR data, it was found that the triflate salt 4b existed as half hydrate where two naked triflate anions presumably polarized one H 2 O molecule. Cognizant that such A – ···H–O–H interactions assisted alkene activation, we performed the experiment with an ultradry 4b under otherwise identical reaction conditions, and the allylsilane activation was found to be extremely slow (Figure , equation 3). Additionally, the 19 F NMR spectrum of 4b recorded for the reaction mixture did not resemble the 19 F chemical shift of triflic acid, suggesting the unique ability of such salts to activate allyl silanes (Figure c).…”
mentioning
confidence: 99%